Dinâmica de grupos funcionais do fitoplâncton em lagos com diferentes estados de equilíbrio. - Silva, Núbia (2016)
Changes in the equilibrium state of shallow lakes can be induced by in water level fluctuations, promoting changes in the trophic state, structure and dynamics of macrophytes and phytoplankton communities. From the temporal analysis of two shallow lakes with different equilibria, this study aimed to: i) evaluate the structure and dynamics of functional phytoplankton groups (FGs) over a macrophyte cover gradient and its relations with environmental variables in small and shallow lake of clear water (Paraiba, Brazil), and ii) to evaluate the composition and structure of phytoplankton functional groups in lakes with different equilibrium states (clear water and turbid water). The main questions associated were: i) There are differences in the composition and structure FGs in macrophyte coverage gradient? and ii) the composition and structure of functional groups account the differences in the structure and equilibrium states of shallow lakes? Water samples were collected for analysis physical, chemical and biological from August 2014 to June 2015. In the lake clear water (Saint Lucia) transparency values were high (≥ 1) throughout the study period, the pH is kept alkaline , temperatures ranged from 27°C to 34°C. It was verified temporal differences in limnological variables only in 2015, while the spatial scale the total biomass showed no significant difference (p≥1). However, the specific composition of FGs responded to this high environmental heterogeneity (expressed by macrophyte cover) indicating spatiotemporal fluctuations in the composition indicated by the canonical correspondence analysis (CCA). CCA showed that the pH (≤0,05), water temperature (≤0,01), total phosphorous (≤0,07) and orthophosphate (≤0 05) influencing the dynamics of functional groups N, K, S1, X1, W2, TD, SN, P. The lake turbid waters (Lagoon Pao) showed very low levels of transparency and photic zone (≤1), by light limitation indicators, and high phosphorus values revealing the potential for eutrophication. This scenario contrasts with Saint Lucia indicated structure and composition of the different functional groups, with only five common functional groups: K, S1, X1, W2 and P. Among the unique functional groups on the Lagoon pao some were composed of potentially toxic cyanobacteria (SN, F LO, D H1) not found in Santa Lucia indicator that the submerged macrophyte cover can function as an inhibitory dominant these species. The CCA showed a clear separation between the environments, with the TD group, N, W2 and S1 related to St. Lucia, typical of clear water. Already Pond Pao, pH, temperature, concentrations of phosphorus, light attenuation coefficient influenced the occurrence of H1, SN, S1, W2, X1, D, LO, mostly represented by common cyanobacteria in eutrophic environments. Therefore, the structure and composition of said functional groups according to the characteristics of the environments studied, showing shallow lakes with different equilibrium states can share similar functional groups. This study confirms the historical data macrophyte cover can operate as cyanobacteria controller, and possible mechanisms associated allelopathy, the decrease in the pellet resuspension, the absorption of nutrients such as phosphorus, among others.